Banks' credit losses and lending dynamics - Peter Raupach; Christoph Memmel (Deutsche Bundesbank, 2021)
Using detailed data of all German banks, we find that banks which have suffered heavy credit losses reduce their corporate lending business by 1.32 euro for each euro lost; with 95% confidence, the effect is between 0.85 and 1.80 euros. This sensitivity is in line with (quite heterogeneous) results of earlier studies but significantly lower than those arising from the assumption of constant leverage. Weakly capitalized banks grant fewer new loans than other banks. We control for credit demand using a new method, the construction of tailored hypothetical bank competitors.
Keywords: G21; 330; Credit losses; Bank lending